Juvenile Delinquency Behavior in Pelang Hamlet, Margorejo Village, Dawe District, Kudus Regency - Sapuan, Edi; Pramono, Suwito Eko; Handoyo, Eko (Universitas Negeri Semarang, 2018)
Juvenile delinquency that occurred in Margorejo village increasingly troubled parents and the surrounding community. The teenagers who are experiencing a transition (transition) are trying to find identity through their daily interactions. This research aims to analyze juvenile delinquency behavior in Pelang Hamlet, Margorejo Village. The focus of this research includes factors causing juvenile delinquency, forms of juvenile delinquency, and ways to overcome juvenile delinquency in Pelang Hamlet, Margorejo Village. This research uses a qualitative approach. Method of collecting data in this research is deep interview, observation, and documentation. The result showed that juvenile delinquency in Pelang Village, Margorejo Village was caused by internal and external factors. Internal factors, which are derived from within the teenagers themselves in the form of weak self-defense. External factors, namely the influence of peers in the community, schoolmates, and playmates, and family. Forms of juvenile delinquency that occur in Hamlet Pelang, including smoking, skipping school, then going to playing billiards or playing chess in stalls, motorbike races, playing cards with bets of money, fighting, drinking, and stealing. The efforts made to overcome juvenile delinquency in Dukuh Pelang are carried out through the role of parents who are optimized and the role of the community through an organization or container established as a place to accommodate teenagers' aspirations, inviting teenagers to participate in social activities. The findings of this research are juvenile delinquency that occurs in the Pelang Hamlet of Margorejo Village when it is associated with Pierre Bourdieu's theory can be categorized that it is not absolutely juvenile delinquency formed by the link between habitus and arena.